Love stage!! Volume 4 - Eiki, Eiki (SuBLime, 2015)
"Mega otaku Izumi and famous actor Ryoma have finally confirmed their feelings for one another. Izumi successfully makes his debut in the entertainment industry, and everything seems to be smooth sailing in both his public and private life. However, as Izumi continues to do unexpectedly well in his new career. Ryoma starts getting nervous when work begins keeping them apart!"--Back cover.